2007
DOI: 10.1017/s1751731107257921
|View full text |Cite
|
Sign up to set email alerts
|

Associations between genetic merit for milk production and animal parameters and the fertility performance of dairy cows

Abstract: Relationships between genetic merit for milk production and animal parameters and various parameters of reproductive performance were examined using multilevel binary response analysis in a study of 19 dairy herds for three successive years, representing approximately 2500 cows per year. The proportion of cows intended for rebreeding that were back in-calf again within 100 days of calving (ICR-100) and the proportion of cows that reappeared again with 365 (RR-365) and 400 days (RR-400) of a previous calving we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
3
18
0
4
Order By: Relevance
“…Indeed, for cows with MY and BCS profiles similar to the simulations with a MY indiv of 35 kg and a BCS calv of 3, Suriyasathaporn et al (1998) obtained 50% of pregnant cows at 125 days post calving (n 5 1404 lactations), whereas Mackey et al (2007) obtained 45% at 118 days post calving (n 5 2500 lactations), which is close to our simulated figures (Figure 5) of 44.5% of pregnant cows at 120 days post calving and 50% at 132 days post calving. However, the cumulative proportion of inseminated cows simulated by our model increased more rapidly than in the observation by Suriyasathaporn et al (1998), who reached a 50% rate of inseminated cows at 95 days post calving, whereas in our simulations the insemination rate reached 50% already by 73 days post calving and 73% by 95 days.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Indeed, for cows with MY and BCS profiles similar to the simulations with a MY indiv of 35 kg and a BCS calv of 3, Suriyasathaporn et al (1998) obtained 50% of pregnant cows at 125 days post calving (n 5 1404 lactations), whereas Mackey et al (2007) obtained 45% at 118 days post calving (n 5 2500 lactations), which is close to our simulated figures (Figure 5) of 44.5% of pregnant cows at 120 days post calving and 50% at 132 days post calving. However, the cumulative proportion of inseminated cows simulated by our model increased more rapidly than in the observation by Suriyasathaporn et al (1998), who reached a 50% rate of inseminated cows at 95 days post calving, whereas in our simulations the insemination rate reached 50% already by 73 days post calving and 73% by 95 days.…”
Section: Discussionsupporting
confidence: 55%
“…These two results showed a lower effect of MY on the CI than our simulations (about 20 days of CI per 10 kg of milk), but the differences in MY were observed during the first 60 days of lactation for Petersson et al (2006) and the first 182 days of lactation for McGowan et al (1996), whereas the differences studied in our simulations concerned the whole 305 days lactation. Mackey et al (2007) showed a higher effect of MY on the CI, with a difference in CI of 7.8 days/1000 kg increase in 305 days lactation, which correspond to an increase of about 24 days/10 kg of MY.…”
Section: Discussionmentioning
confidence: 91%
“…The practice of once-daily milking limits the expression of milk production potential and the mobilization of reserves without degrading the intake capacity, and has a comparatively favourable impact on reproduction performance (Ré mond and Pomiè s, 2005). Finally, the rates of success at AI are rather better in cows that do not express their milk production potential (Mackey et al, 2007) because of insufficient body condition at calving or a lack of feed allocation early in lactation (this study). It is important to improve our understanding of the complex relationship between body condition score at calving, the level of nutritive supply at the beginning of lactation and the expressed milk production potential, as well as the effects on the functions of 'lactation' and 'reproduction'.…”
Section: Discussionmentioning
confidence: 75%
“…However, the success of this aggressive genetic selection for production, predominantly within the North American Holstein Friesian genotype, has resulted in increased incidence of nutritional and metabolic problems at the beginning of lactation. More generally, these developments in selection have increased feed requirements of high genetic potential animals throughout their lactation, and resulted in a clear deterioration in other functions such as the capacity to reproduce (Barbat et al, 2005;Mackey et al, 2007). By contrast, dual-purpose breeds and animals selected on multiple criteria are characterized by lower milk production potential while preserving other zootechnical capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on feeding management While dealing with impaired reproductive performance of dairy cows, genetic factors (Mackey et al, 2007), nutrition (Robinson et al, 2006), health of the cow (Collard et al, 2000) and work organisation (Zaaijer and Noordhuizen, 2003) are very often referred to. These four fields are closely connected together.…”
Section: Resarch Approaches On the Links Between Reproduction And Nutmentioning
confidence: 99%